Effect of elexacaftor-tezacaftor-ivacaftor on nasal potential difference and lung function in Phe508del rats - Reyne, Nicole; Cmielewski, Patricia; McCarron, Alexandra; Smith, Ronan; Schneider-Futschik, Elena; Eikelis, Nina; Pirakalathanan, Piraveen; Parsons, David; Donnelley, Martin (Frontiers in Pharmacology, 2024)
Phe508del is the most common cystic fibrosis transmembrane conductance regulator (CFTR) gene variant that results in the recessive genetic disorder cystic fibrosis (CF). The recent development of highly effective CFTR modulator therapies has led to significant health improvements in individuals with this mutation. While numerous animal models of CF exist, few have a CFTR mutation that is amenable to the triple combination therapy elexacaftor-tezacaftorivacaftor (ETI). This study measured nasal potential difference, lung mechanics (via flexiVent), and lung ventilation (via X-ray Velocimetry) to establish whether Phe508del rats are responsive to ETI. Chloride ion transport in nasal airways was restored in Phe508del rats treated with ETI, but neither lung mechanics nor ventilation were significantly altered. These findings validate the usefulness of this rat model for future investigations of modulator therapy in CF.